Engineering with rubber : how to design rubber components - Gent, Alan N. (Hanser Publishers, 2012)
This book provides the beginning engineer with the principles of rubber science and technology: what rubber is, how it behaves, and how to design engineering components with rubber. It introduces the reader to the principles on which successful use of rubber depends and offers solutions to the questions engineers in rubber processing face every day: - How is an elastomer chosen and a formulation developed - Why is rubber highly-elastic and relatively strong - How to estimate the stiffness and the strength of a product - How to guarantee high quality and durability The authors describe current practices in rubber engineering. At the end of each chapter, sample questions and problems (together with solutions) are provided, allowing the reader to gauge how well he/she has mastered the material.